The Musicality of Gamelan Gong Kebyar Mepacek as a North Bali Traditional Music Identity - Kadek Angga Wahyu Pradana; I Wayan Rai S; I Wayan Suherta (RIRAI Publisher, 2023)
The purpose of this research was to reveal the musicality of Gamelan Gong Kebyar Mepacek as the identity of North Bali's traditional music. Many researchers have carried out numerous research studies on Gong Kebyar. However, there has not been a single study on the musicality of Gong Kebyar Mepacek's gamelan, which has caused this gamelan to become the hallmark of North Bali's traditional music. How is Gamelan Gong Kebyar Mepacek's musicality measured?. What is the influence of the musicality of Gamelan Gong Kebyar Mepacek on the traditional Balinese music being played? This research was conducted using qualitative methods from the perspective of ethnomusicology. All data that has been collected through observation, interviews, and literature studies is analyzed using ethnomusical theory. The results of the study show that the musicality of Gamelan Gong Kebyar Mepacek has shorter pitch repertoire, a faster closing technique, a faster gending tempo, and a louder gamelan sound compared to Gong Kebyar gamelan in general. To measure the pitch of the Gong Kebyar mepacek gamelan tuner, a tuner was used in the Studio One 5 digital audio workstation (DAW) application. The effect of this mepacek gamelan model on the traditional music played can be seen in the tempo, which is the maximum speed that can be achieved by the musicians playing the gamelan. This means that by pacing the gamelan blades, the drummers do not need to wait long to close the gamelan chords.